The Traveler, the Tower, and the Worm : The Reader as Metaphor - Manguel, Alberto (Book collections on Project MUSE., 2013)
The author examines metaphors of readers and reading from literatures across centuries and the globe, from the ancient epic Gilgamesh to the World Wide Web, from the adventures of Ulysses to the tragedy of Emma Bovary, and he considers how these metaphors reflect the cultures that invent them.